Effects of the Manufacturing Methods on the Mechanical Properties of a Medical-Grade Copolymer Poly(L-lactide-co-D,L-lactide) and Poly(L-lactide-co-ε-caprolactone) Blend - Mariana Rodriguez Reinoso (MDPI AG, 2021)
Biocompatible and biodegradable polymers represent the future in the manufacturing of medical implantable solutions. As of today, these are generally manufactured with metallic components which cannot be naturally absorbed within the human body. This requires performing an additional surgical procedure to remove the remnants after complete rehabilitation or to leave the devices in situ indefinitely. Nevertheless, the biomaterials used for this purpose must satisfy well-defined mechanical requirements. These are difficult to ascertain at the design phase since they depend not only on their physicochemical properties but also on the specific manufacturing methods used for the target application. Therefore, this research was focused on establishing the effects of the manufacturing methods on both the mechanical properties and the thermal behavior of a medical-grade copolymer blend. Specifically, Injection and Compression Molding were considered. A Poly(L-lactide-co-D,L-lactide)/Poly(L-lactide-co-ε-caprolactone) blend was considered for this investigation, with a ratio of 50/50 (w/w), aimed at the manufacturing of implantable devices for tendon repair. Interesting results were obtained.